(untitled) (Baghdad Science Journal, 2016)
Our goal in this research, some new nucleoside analogues was synthesized. Starting from ?-D glucose which was converted to per acetylated ?-D gluco pyronoside then converted to active from(1-Bromo Sugar (2) as a sugar moiety.The base moiety 2-substituted benzimidazole was prepared from condensation of phenylene diamine with different aromatic aldehydes, which were subjected to amino alkylation via Mannich reaction forming new nucleobase derivatives. Condensation of nucleobase with bromo sugar through nucleophilic substitution of anomeric carbon with nitrogen forming new protected nucleoside analogues then hydrolyzed with sodium methoxide in methanol to obtain our target, the free nucleoside analogues. All prepared compound were identified by FT-IR Spectroscopy and some of them with H1 –NMR and C13-NMR Spectroscopy. The synthesized nucleoside analogues were screened for their antibacterial activity in vitro against four types of bacteria including, Bacillus Staphylococcus, aureus (Gram Positive), E.Coli and Pseudoman as (Gram Negative).Also were screened against four types of Fungi (Aspergines flurs, Aspergillus fumgntnts, Aspergillus niger and pencillum).